Arsenic contamination of groundwater in the Kathmandu Valley, Nepal, as a consequence of rapid erosion (Journal of Nepal Geological Society, 2010)
Elevated levels of arsenic (As) in groundwater in the flood plain of the Ganges River have been well-documented over the past decades. The objective of this study was to measure As and the transition elements normally associated with As in the Kathmandu Valley in Nepal, a heavily populated tectonic valley in the upper reaches of the Ganges River system. Water samples were collected from six shallow tubewells (depth < 50 m), eight deep tubewells and 13 dug wells and stone spouts. Electrical conductivity, temperature and pH were measured on-site and concentrations of As, Fe, Cu, Ni, Co, Mn, Zn and Cr were measured with a spectrophotometer. Five tubewells and four dug wells had As levels exceeding the Nepal Interim Standard (As = 0.05 mg/L). There was no statistically significant clustering of As levels either with depth or horizontal location. Arsenic was uncorrelated with either Fe (R2 = 0.096), Mn (R2 = 0.0004) or any combination of transition elements (R2 < 0.083), which is inconsistent with both the reduction-dissolution and the sulfide oxidation models for As release. The geometric mean As level of groundwater (As = 0.015 mg/L) was indistinguishable from the geometric mean As level of surface water (As = 0.013 mg/L) obtained from 48 river samples from the Kathmandu Valley in a previous study. We are suggesting that elevated groundwater As results not from subsurface redox conditions, but from losing streams with elevated As, which is a consequence of rapid erosion caused by a combination of monsoon climate, tectonic uplift and deforestation.